2019
DOI: 10.1002/smj.3063
|View full text |Cite
|
Sign up to set email alerts
|

Under pressure: Reputation, ratings, and inaccurate self‐reporting in the nursing home industry

Abstract: Research Summary: This paper examines firms' strategic responses to reputational pressures in a critical healthcare domain-the U.S. nursing home industry. We investigate whether organizations improved in terms of care quality following an exogenous change in the required number of nursing hours associated with star-based ratings to which nursing homes are subject. We show that although firms at risk of losing a star tended to self-report higher staffing levels after the policy change, these reported increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Publicly-owned hospitals prioritize patients who are representative of voter sentiment. We know very little about how organizational form affects the propensity of and type of misconduct, and this paper also contributes to the growing literature on misconduct related to health care organizations (Snyder, 2010;Ody-Brasier & Sharkey, 2019). Douthit, Millar, and White (this issue) examine fraudulent "doubling" of taxi fares in New York City, where drivers falsely claim that a trip took them outside the city limits, allowing them to double the rate for an unneeded trip back to the city limits.…”
Section: Archival Data Analysismentioning
confidence: 99%
“…Publicly-owned hospitals prioritize patients who are representative of voter sentiment. We know very little about how organizational form affects the propensity of and type of misconduct, and this paper also contributes to the growing literature on misconduct related to health care organizations (Snyder, 2010;Ody-Brasier & Sharkey, 2019). Douthit, Millar, and White (this issue) examine fraudulent "doubling" of taxi fares in New York City, where drivers falsely claim that a trip took them outside the city limits, allowing them to double the rate for an unneeded trip back to the city limits.…”
Section: Archival Data Analysismentioning
confidence: 99%
“…Organizational resistance to ratings can take the form of 'gaming', whereby organizations provide incomplete or inaccurate information to the evaluator to improve their rating. Such gaming undermines the motivation behind evaluation criteria (Espeland & Sauder, 2007) as shown for example in a study of nursing homes in the United States, where higher reported staff numbers necessary to obtain high ratings did not lead to improvements in care outcomes (Ody-Brasier & Sharkey, 2019). Organizations not only 'internalize' expectations from rating agencies (Espeland & Sauder, 2007) but also interpret rankings in ways that best serve their needs.…”
Section: Anxiety: Resisting Csr Ratingsmentioning
confidence: 99%
“…Given the proliferation of these rating systems and their intention to drive change in behavior, understanding how organizations respond to ratings has become an important area of scholarly inquiry (Tolbert, 2018). To date, scholarship on reactivity to ratings has illustrated how unfavorable evaluations can drive improvements in subsequent performance (Jin and Leslie, 2003; Chatterji and Toffel, 2010; Sharkey and Bromley, 2015; Rowley, Shipilov, and Greve, 2017; Ody-Brasier and Sharkey, 2019). From a theoretical standpoint, this research stream has generally reasoned that receiving a favorable rating is beneficial because it enhances external perceptions of the organization, thus strengthening its reputation (Lange, Lee, and Dai, 2011).…”
mentioning
confidence: 99%
“…1 Some scholars, for example, have noted how “high scores on a rating” generally lead to a “positive reputation,” while “low scores on a rating” generally lead to a “negative reputation” (Rowley, Shipilov, and Greve, 2017: 818). Because strong reputations are presumed to be a valuable resource (Fombrun and Shanley, 1990; Barney, 1991; Roberts and Dowling, 2002), and positive evaluations are expected to generate positive perceptions that enhance organizational reputation (Rindova et al, 2005; Espeland and Sauder, 2007; Bermiss, Zajac, and King, 2014), scholars have typically concluded that organizations will strive to improve or sustain a certain performance level to avoid the negative consequences of a poor rating and obtain or maintain the benefits of a good rating (Sharkey and Bromley, 2015; Ody-Brasier and Sharkey, 2019).…”
mentioning
confidence: 99%